WHAT IS THE BEHAVIOR OF STUDENT SAVINGS? - Negara, Andi Kusuma; Erdawati, Lena; Hardianto, Alit Millinia; Mubarok, Ahmad Zakki (Digital Business Journal, 2025)
This study aims to test and analyze the influence of financial knowledge, financial attitude, and income on student saving behavior. The independent variables in this study were financial knowledge, financial attitude and income, while the dependent variables in this study were saving behavior. This study uses primary data by providing a number of questionnaires to management students of the Faculty of Economics and Business, University of Muhammadiyah Tangerang. The number of samples in this study was 89 respondents. Furthermore, the data that has been collected is analyzed by multiple linear regression, The regression test results show that there is a significant influence of financial knowledge and financial attitude variables on saving behavior, proven. This is evidenced by the t-value calculated on the financial knowledge variable of 3,599 with a significance of 0.001 and the financial attitude of 4,120 with a significance of 0.000 so that the t-value is calculated above the t table and the significance is below 0.10. Therefore, it can be concluded that there is a significant influence of financial knowledge and financial attitude variables on saving behavior. Meanwhile, there is an influence of income variables on saving behavior, which is not proven. This is evidenced by the t-value calculated on the income variable of 0.820 with a significance of 0.414 so that the t-value calculated below the t table and the significance above 0.10. Therefore, it can be concluded that there is no significant influence of income variables on saving behavior.